Occurrence of aflatoxin contamination in cow milk at different seasons in urban and rural areas of the Sidama Zone, Southern Ethiopia - Tolosa Taye; Mestawet Taye; Tegene Neggese; Wubshet Tefera (Food and Agricultural Immunology)
This study was conducted in 2023 to determine AFM1 contamination of cow milk in the Sidama zone, southern Ethiopia. A total of 240 milk samples were analysed by the Enzyme-Linked Immunosorbent Assay. Out of 240 milk samples, 75% were positive for AFM1 with a range of 0.00014–1.16 µg/L and mean concentration 0.04 ± 0.13 µg/L, which was lower than the EU and US standards. AFM1 was significantly higher (P < 0.05) in the dry season (0.06 ± 0.17 µg/L) than rainy season (0.02 ± 0.03 µg/L). Only 11% and 2% of the milk samples were above the EU and US standard respectively. Future research on AFM1 should focus on buttermilk since it is the most common form of milk consumed in the area. In conclusion, care should be taken in children’s milk consumption since the AFM1 from the analysed raw cow milk in the study area is found to be above standard for children, which might have public health significance.